(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article examines the strategic foundations of innovation management in modern organizations and analyzes the systemic problems limiting innovation effectiveness. The research focuses on organizational, managerial, financial, technological, and human-capital-related barriers affecting innovation processes. Particular attention is devoted to digital transformation, innovation-oriented organizational culture, strategic planning, and data-driven management systems. The study applies analytical, comparative, and statistical methods to evaluate innovation management efficiency and identify the main factors influencing organizational competitiveness. Research findings demonstrate that innovation effectiveness depends not only on technological resources but also on strategic integration, flexible management systems, qualified human capital, and digital infrastructure. The article also explores statistical indicators related to innovation cycles, return on investment, innovation productivity, and international innovation practices. The findings confirm that integrated innovation management systems significantly strengthen enterprise sustainability, operational effectiveness, and long-term competitive advantage in the digital economy.